(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the association of intermittent fasting (IF) and coffee intake in Wistar rats pre-treated with a high-fat diet. Newborn Wistar rats were used, randomly divided into 4 groups: Control (CO, commercial feed), Control+Coffee (CA, commercial feed+coffee), Fasting (IF, 24 hours feeding/24 hours fasting), Fasting+Coffee (IFCA, 24 hours feeding/24 hours fasting+coffee). The animals were pre-treated with a hyperlipidic diet for 30 days. The coffee administered to the animals was 100% Arabica, at a dose of 0.5 mL by gavage daily. Weight was measured weekly throughout the experiment and after euthanasia, subcutaneous and visceral fat were removed and weighed. Glucose and insulin rates, lipid profile and liver histology were analyzed. The fasting groups had significantly lower results in weight and fat mass gain, better lipid profile and lower hepatic fat deposition. Lower collagen deposition was observed in the groups that ingested coffee, as well as a lower moisture content. From the results obtained, it can be concluded that the combination of interventions can be beneficial in reducing weight gain and body fat, in addition to having a synergistic effect in reducing hepatic steatosis in rats pre-treated with a high-fat diet.